Antecedent and Consequences of Green Self-Efficacy: Cases from Gen Y Employees in Retail Industries - Aldisa, Syafira; Emilisa, Netania; Arafah, Mutiara Jihad; Mariaulfa, Inge (Golden Ratio of Human Resource Management, 2025)
This research explores the impact of Green Transformational Leadership (GTL) and Green Perceived Organizational Support (GPOS) on Green Entrepreneurial Intention (GEI) among Generation Y employees in the retail sector of South Tangerang, with Green Self-Efficacy (GSE) serving as a mediating variable. Using data collected from 120 respondents, the analysis reveals that GTL and GPOS positively influence GSE. Nevertheless, only GTL directly contributes to GEI, whereas the influence of GPOS on GEI is mediated through GSE. These outcomes emphasize the critical role of leadership and organizational backing in enhancing employees' confidence to pursue green entrepreneurship. The study concludes that strengthening green self-efficacy and promoting environmentally conscious leadership are essential strategies to support sustainable innovation within retail organizations.